2019
DOI: 10.1371/journal.pone.0219916
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of automated ultrasonographic detection of bladder diameter for estimation of bladder urine volume

Abstract: Bladder urine volume has been estimated using an ellipsoid method based on triaxial measurements of the bladder extrapolated from two-dimensional ultrasound images. This study aimed to automate this process and to determine the accuracy of the automated estimation method for normal and small amounts of urine. A training set of 81 pairs of transverse and longitudinal ultrasound images were collected from healthy volunteers on a tablet-type ultrasound device, and an automatic detection tool was developed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…However, the analysis showed that a high contrast is crucial to prevent segmentation artifacts. This is underlined by the comparison with earlier work on the use of CNNs for bladder segmentation from ultrasound data [26,27], where a higher correlation between the automatically determined and the manually segmented bladder volumes was obtained. However, it should be mentioned, that the cited work was based on the use of high-end clinical ultrasound devices, which provide higher contrast, and two orthogonal B-mode images were acquired for obtaining quantitative values for the bladder volume [26].…”
Section: Discussionmentioning
confidence: 58%
“…However, the analysis showed that a high contrast is crucial to prevent segmentation artifacts. This is underlined by the comparison with earlier work on the use of CNNs for bladder segmentation from ultrasound data [26,27], where a higher correlation between the automatically determined and the manually segmented bladder volumes was obtained. However, it should be mentioned, that the cited work was based on the use of high-end clinical ultrasound devices, which provide higher contrast, and two orthogonal B-mode images were acquired for obtaining quantitative values for the bladder volume [26].…”
Section: Discussionmentioning
confidence: 58%
“…Each dimension is the maximum diameter derived from the transverse and longitudinal views using 2-D ultrasound imaging equipment. The volume estimation method of the bladder is mainly recommended as an ellipsoid because of its relatively accurate results and ease of application [ 28 , 29 ]. Among the shapes assumed as the bladder, the ellipsoid can be derived by a single quadric surface equation.…”
Section: Methodsmentioning
confidence: 99%
“…The number of channels in each convolutional layer of the VGG16‐like CNN was one‐fourth of that of the VGG16. The above procedure was performed with reference to a previous study (Matsumoto et al, 2019).…”
Section: Methodsmentioning
confidence: 99%